From designing diets for animals to designing food of animal origin – overview. Issue 1 (October 2021) - Markovic, R; Baltic, M Z; Radulovic, S; Peric, D; Jovanovic, D; Starcevic, M; Sefer, D
Abstract: In recent times, food is not only observed from the point of view of the required intake for growth, development and regeneration of the body, but also has a leading role in the quality of human life. Therefore, the diet focuses on optimizing the daily intake of both nutrients and non-nutritive ingredients of food, all in order to preserve health and, above all, reduce the risk of chronic non-communicable diseases. Functional food can be considered food that has been scientifically proven to have a positive effect on certain body functions (in addition to the usual nutritional value) that contribute to human health and reduce the risk of disease. At the same time, it is important that the food has a standard form and that the positive effect on health is manifested by consuming the usual amount of food. The functionality of food is achieved by the presence in it of bioactive components (one or more) which have been scientifically proven to have positive effects on human health in the quantities in which they are present in food. The nutritional value of foods of animal origin depends on many factors, but certainly animal diet has the greatest impact. In human nutrition the so-called designed products of animal origin (meat, milk, eggs) are used, which are due to the specific animal diets enriched with n-3 fatty acids, vitamins, carotenoids or trace elements. Today, there are nutritional strategies by which we can access functional foods for the purpose of health promotion.